Polycladida phylogeny and evolution: integrating evidence from 28S rDNA and morphology - Bahia, J.; Padula, V.; Schrödl, M. (Organisms Diversity & Evolution, 2017)
Polyclad flatworms have a troubled classification history, with two contradicting systems in use. They both rely on a ventral adhesive structure to define the suborders Acotylea and Cotylea, but superfamilies were defined according to eyespot arrangement (Prudhoe’s system) or prostatic vesicle characters (Faubel’s system). Molecular data available cover a very limited part of the known polyclad family diversity and have not allowed testing morphology-based classification systems on Polycladida yet.We thus sampled a suitable marker, partial 28S ribosomal DNA (rDNA), from Polycladida (19 families and 32 genera), generating 136 new sequences and the first comprehensive genetic dataset on polyclads. Our maximum likelihood (ML) analyses recovered Polycladida, but the traditional suborders were not monophyletic, as the supposedly acotyleans Cestoplana and Theama were nested within Cotylea; we suggest that these genera should be included in Cotylea. The partial 28S rDNA trees were generally well supported and robust but in conflict with both Faubel’s and Prudhoe’s superfamilies. Therefore, we compiled morphological and anatomical characters for all taxa used and examined their distribution on our molecular tree. Combining morphological and molecular evidence, we redefined polyclad superfamilies. Acotylea contain tentaculated and atentaculated groups and is now divided in three superfamilies. The suborder Cotylea can be divided in five superfamilies. In general, there is a trait of anteriorization of sensory structures, from the plesiomorphic acotylean body plan to the cotylean gross morphology. Traditionally used characters, such as prostatic vesicle, eyespot distribution, and type of pharynx, are all homoplastic and likely have misled polyclad systematics so far.